PENDIDIKAN KESEHATAN TENTANG HIPERTENSI DAN POLA HIDUP SEHAT PADA WANITA USIA SUBUR DI RT 05 RW 06 KELURAHAN LENGKONGSARI KECAMATAN TAWANG KOTA TASIKMALAYA - Rismawati, Sariestya; Putri, Dinda Hermalia (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
Hypertension is currently listed as one of the diseases that cause premature death in the world. Generally hypertension is found in people with old age. However, at this time, hypertension is also commonly found in reproductive age, one of which is in women of childbearing age (WUS). Data shows that the incidence of hypertension in WUS in Indonesia is around 36.9%. Apart from age and family history, hypertension can also occur due to unhealthy living habits such as smoking habits, lack of fruit and vegetable consumption, lack of physical activity, use of hormonal contraception and ect. The aim of this study was to increased the knowledge about hypertension and a healthy lifestyle in Women of Reproductive Age (WUS). The community service method used in this study is in the form of health education with health cheeck and activities. The result showed that there was an increase in knowledge about hypertension and a healty lifestyle. Suggestions for women of chieldbearing age can maintain the health of themselves and their families by living a healthy lifestyle, regular check-up and empowering themselves by increasing knowledge about health from various references.